Case report: A case study of neoadjuvant immunochemotherapy for locally advanced esophageal squamous carcinoma - Liu, Xiong; Wang, Maoqi; Meng, Deyuan; Tang, Yuntao; Shi, Qingtong (Frontiers in Oncology, 2024)
In locally advanced esophageal cancer, the controversy over the two traditional treatment modalities, neoadjuvant radiotherapy and neoadjuvant chemotherapy, has been unending and also challenged by the addition of neoadjuvant immunotherapy. Neoadjuvant immunotherapy has led to an increasing diversity of neoadjuvant combination treatment modalities, among which neoadjuvant immunochemotherapy has emerged, with current clinical studies initially demonstrating its efficacy and safety.We report a case of a patient with locally advanced esophageal cancer who underwent two cycles of neoadjuvant immunochemotherapy and underwent successful surgery and achieved a pathological complete remission pCR. A 73-year-old elderly female patient presented with progressive dysphagia for more than 1 month with an ECOG score of 1. After completing gastroscopy + pathological biopsy, chest enhanced CT, barium esophageal meal and PET-CT and other related examinations, the clinical diagnosis was thoracic segmental esophageal low-differentiated squamous carcinoma cT2N2M0 stage III. After multidisciplinary discussion of the comprehensive treatment plan, two cycles of neoadjuvant therapy were given on 2023-02-16 and 2023-03-09, and the treatment plan was as follows: cisplatin 30mg d1-3 + albumin paclitaxel 200mg d1, 100mg d8 + Sintilimab 200mg d4, q3w, and after the neoadjuvant therapy the patient underwent an imaging examination, and the chest-enhanced CT suggested that the lesion range was significantly reduced compared with the previous, mediastinal lymph nodes were partially reduced, then thoracoscopic radical esophageal cancer surgery was performed on 2023-04-23, and pathological complete remission pCR was achieved by pathological evaluation, and the postoperative diagnosis was thoracic segmental esophageal hypofractionated squamous carcinoma ypT0N0M0. Two cycles of adjuvant immunochemotherapy were performed after surgery on